LIMBAH PERCA SEBAGAI PENGGERAK INSPIRASI INDUSTRI FASHION MASA DEPAN - Michelle Michelle; Franky Liauw (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
The world of fashion is evolving and changing, making it a means for individuals to express themselves to the outside world. Before the pandemic of COVID-19, there was a fast-fashion trend, which contributed to an increase in production and left behind non-reusable fabric scraps. In 2019, DKI Jakarta, fabric waste had an impact on the East Ancol Beach in Pademangan, contaminating its shores and waters. This is concerning due to the negative effects on the environmental ecosystem and the health of nearby residents. To address this issue, an architecture program initiated the utilization of fabric scraps as a resource through processing, production,and clothing sales. The program aims to transform fabric waste into materials that hold added value. Through qualitative design methods and an educational approach, this architecture program was established to provide understanding and inspiration to the younger generation to innovate in creating unique products by utilizing fabric scraps. The existence of this program is expected to create awareness of the importance of managing fabric waste as a renewal. This program also aims to ignite a spirit of innovation and creativity among the community. By utilizing fabric scraps as a valuable resource and promoting environmentally friendly practices in the fashion industry, this program encourages the adoption of sustainable practice. Through collaboration between the younger generation and the community as producers and consumers, a collective awareness is created to preserve the environment and establish a responsible and future-oriented fashion industry. Keywords: education; fabric scrap; fashion; innovation; wast Abstrak Aktivitas dunia fashion semakin berkembang dan berubah, menjadikannya sebagai sarana untuk mengekspresikan diri seseorang kepada dunia luar. Sebelum masa pandemi Covid-19 berlangsung, terjadi fenomena fast-fashion trend yang mencuat, dimana produksinya telah berkontribusi pada peningkatan dan menyisakan limbah kain perca yang tidak dapat digunakan kembali. Tahun 2019 di DKI Jakarta, limbah perca berdampak ke lingkungan Pantai Timur Ancol, Pademangan yang ditemukan di bibir dan perairan pantai. hal ini mengkhawatirkan karena dampak negatifnya terhadap ekosistem lingkungan dan kesehatan manusia yang tinggal disekitarnya. Dalam mengatasi permasalahan tersebut, program arsitektur menginisiasi penggunaan kain perca sebagai sumber daya melalui pengolahan, produksi, dan penjualan pakaian. Program ini bertujuan untuk mengubah limbah perca menjadi bahan yang memiliki nilai tambah. Melalui metode perancangan kualitatif dan pendekatan edukatif, program arsitektur ini dibentuk untuk memberikan pemahaman serta inspirasi kepada generasi muda dalam berinovasi menciptakan produk unik melalui pemanfaatan limbah perca. Keberadaan program ini, diharapkan adanya kesadaran akan pentingnya pengelolaan limbah perca menjadi sebuah kebaharuan. Program juga bertujuan untuk membangkitkan semangat inovasi dan kreativitas di kalangan masyarakat. Pemanfaatan limbah perca sebagai sumber daya yang berharga dengan mendorong adopsi praktik ramah lingkungan dalam industri fashion. Melalui kolaborasi antara generasi muda dan masyarakat sebagai produsen dan konsumen, tercipta kesadaran kolektif untuk menjaga kelestarian lingkungan dan menciptakan sebuah industri fashion yang bertanggung jawab dan berwawasan masa depan.